Teachers’ Involvement in Managerial Decision-Making Processes in Schools - Tikiawati, Tikiawati; Sulistyaningrum, Siti Drivoka (International Journal of Educational Research & Social Sciences, 2024)
Due to the global movement of educational reforms, teachers’ new empowered roles in school had been discussed and promoted. In schools, effective teacher involvement in decision making can be an approach to practicing participatory management. Thus, the author systematically searched for and synthesized evidence from certain studies related to teachers’ involvement in school managerial decision-making to encourage research on diverse participation in school administration. This paper uses a systematic literature review, which is a research method for identifying and critically reviewing other related research, as well as for collecting and interpreting data from such studies. Subsequently, managerial decision-making processes, Strategies of participation in decision-making at the school level, and factors that influence teachers’ involvement in the decision making will be discussed in this study. It is assumed that educational leaders should encourage ways of involvement in decision-making that improve teachers' participation in managerial decisions concerning their roles and opportunities for development and allow for further sharing on issues concerning school management. Then, the results can be used to determine whether the effects of teacher involvement constant across studies and discover whether studies conducted in one context show significantly different results from those conducted in other contexts.